Anthropology. current and future developments - Bednarik, Robert G. (Anthropology: Current and Future Developments., 2015)
The First Mariners comprehensively describes the archaeological background and relevant issues of the project and features an extensive pictorial record, of both the experiments and the archaeological basis of this research - giving a unique experience to readers interested in understanding the earliest marine adventurers from a historical and technical perspective.